Are Nonprofits Obsolete? - Gathuo, Shiko (American Journal of Humanities and Social Sciences, 2015)
Can the nonprofit sector survive the barrage of government regulations, the fast changing environment, the changing priorities of donors and beneficiaries, the democratized nature of fundraising and a host of other internal and external factors? The nonprofit sector is threatened by its very nature, which is complex and seems to go against the established principles of successful organizations. At the same time the larger outer environment has continued to wreak havoc on a sector that is already internally weak. Can the nonprofit sector, as organized, continue to exist? This paper discusses the internal weaknesses inherent to the nonprofit sector including funding, legal organization, nature of nonprofit work, workers and clients, as well as the external threats to the sector including inter-sectoral competition, regulations and the changing global economic landscape. To stay relevant, nonprofits must adapt to the changing outer environment by evolving internally.